Learning the hard way : masculinity, place, and the gender gap in education - Morris, Edward W., 1973- (Rutgers series in childhood studies., 2012)
In Learning the Hard Way, Edward W. Morris explores and analyzes detailed ethnographic data to examine the purported gender gap between boys and girls in educational achievement at two low-income high schools-one rural and predominantly white, the other urban and mostly African American. He explains how race, class, and geographic location combine to influence and complicate the construction of gender identities in high school students and affect the respective academic performance of the stud.